1996
DOI: 10.1055/s-2007-972890
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 4h Preexercise High Carbohydrate and High Fat Meal Ingestion on Endurance Performance and Metabolism

Abstract: The effect of a single high carbohydrate meal (HCM) and high fat meal (HFM) given 4 h before cycling exercises was determined for performance and metabolism. On the morning of the day of the trial, 10 endurance-trained collegiate males consumed either a single HCM (4669 kj; 79% CHO, 10% F and 11% P) or HFM (4711 kj; 30% CHO, 61% F and 9% P) as a 4 h preexercise meal. The intensity of exercise required was 65% of the maximal oxygen consumption (VO2max) for the first 120 min of exercise, followed by an increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
2
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 3 publications
2
20
2
1
Order By: Relevance
“…However, again insulin was not analysed postprandially so similar caveats to the present investigations may be warranted. This contrasts the observations from previous research [ 21 ] that noted significant elevations in insulin concentrations after a HCM relative to [ 11 ] . A possible explanation for the performance impairments with these studies is the high fat diets they utilise may result in a reduction in muscle and liver glycogen stores prior to exercise.…”
contrasting
confidence: 99%
See 3 more Smart Citations
“…However, again insulin was not analysed postprandially so similar caveats to the present investigations may be warranted. This contrasts the observations from previous research [ 21 ] that noted significant elevations in insulin concentrations after a HCM relative to [ 11 ] . A possible explanation for the performance impairments with these studies is the high fat diets they utilise may result in a reduction in muscle and liver glycogen stores prior to exercise.…”
contrasting
confidence: 99%
“…An increase in β-hydroxybutyrate concentration was also found throughout exercise following ingestion of the HFM, which may refl ect stimulation of hepatic ketosis due to greater levels of fat metabolism. This result refl ects similar observations in cycling [ 21 ] . The presence of elevated concentrations of fat metabolites following the consumption of a HFM relative to the HCM may be attributed to the greater availability of fat following the HFM.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Fats are supplied by meals, and also by adipose tissues, but CHO must be acquired from meals before exercise because little is stored as glycogen in the liver or muscle tissue. Previous studies have been conducted on the ergogenic effects of CHO feeding before exercise (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). It was reported that CHO solution (such as glucose and maltodextrin) feeding before exercise can improve exercise performance through enhanced endurance exercise capacity (2,4,5,10).…”
mentioning
confidence: 99%